RENCANA PENARIKAN DANA HALAMAN III DIPA SEBAGAI FUNGSI KONTROL PELAKSANAAN ANGGARAN PADA KEMENTERIAN/LEMBAGA DI SULAWESI SELATAN - Usman, Firman; Hartanto, Tomi; Romadhon, Ahmad (Transpublika Publisher, 2023)
The Fund Withdrawal Plan (RPD) at the Ministry of State / Institution is an instrument that indicates the intention to use state funds within a certain period of time to support the financing of previously scheduled activities. However, the implementation of the RPD in South Sulawesi is still not optimal, as seen from the significant difference between the realized budget and the Fund Withdrawal Plan reflected in the budget revision on Page III of DIPA. This shows that activity planning in various work units is not fully in line with the predetermined Fund Withdrawal Plan. In addition, the low control function in the Work Unit also affects budget implementation, so it is necessary to increase the capacity of Human Resources (HR) in the region. As the Regional Chief Economist and Financial Advisor in the Regional Office of DGTb, the strategic role in overcoming this problem becomes increasingly important. It is necessary to increase the capacity of human resources in the relevant Work Units so that they can conduct in-depth analysis of the Fund Withdrawal Plan on Page III of DIPA. Strengthening the role of functional officials is also needed to ensure that the recommendations from the analysis are of high quality.